The Startup for Education in the 4th Industrial Revolution - Fauziyati, Dini (Proceeding International Conference on Science and Engineering, 2019)
According to Merriam-Webster, start-up means “the act or an instance of setting in operation or motion” or “a fledgling business enterprise.” The American Heritage Dictionary suggests it is “a business or undertaking that has recently begun operation.” One thing that can all agree on: the key attribute of a startup is its ability to grow. As Graham explains, a startup is a company designed to scale very quickly. It is this focus on growth unconstrained by geography which differentiates startups from small businesses. Recently Indonesia was shocked by the industrial revolution 4.0. This era was marked by a start-up business. One of the Indonesian youth who successfully released the startup was Umar Usman. He is a student from the University of Indonesia which is International Relations Department with his teacher room finding. Since childhood, Usman aspired to become a teacher. That’s why Umar Usman is motivated so that teachers can provide the widest possible benefits so that science and technology-based science findings are needed. From that sense of awe and Umar Usman wanted to give something to the teachers and students namely the teacher room application. This study t ries to dig up information with literature review to find out how startups in education and their contribution to education.